A etnomatematica e suas contribuições para o conteúdo da matemática escolar - Chaves, Filipe Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
In this research we set out to understand the Ethnomathematics Program such as it is said by some authors of Mathematics Education. To this end we conducted an exploratory study. The objective of to study this program is to analyze its contribution to understanding of the content of mathematics in the school environment. The authors studied are Ubiratan D'Ambrosio, considered the precursor of the Ethnomathematics Program and researchers as Paulus Gerdes, Maria do Carmo Santos Domite, Eduardo Sebastiani Ferreira and Gelsa Knijnik, that develop research in Ethnomathematics and may contribute to the comprehension of what in the study we intend to do. Although recourse to authors of Education and Education Philosophy as Maria Aparecida Viggiani Bicudo and Joel Martins to intend the idea of curriculum and its importance in the school environment. The study carried showed that the Ethnomathematics Program goes beyond of to explicit the mathematical knowledge produced by cultural groups, transcending the description of procedures that reveal the construction of knowledge hitch to school subjects. That is, the program seeks the valuing the human being, concerning itself with the construction of a worthy citizen and able to relate with their natural environment, social and intellectual

Nesta pesquisa nos dispusemos a compreender o Programa Etnomatemática tal qual ele é apresentado por alguns autores de Educação Matemática. Para tanto realizamos um estudo exploratório. O objetivo de estudar tal programa é analisar sua contribuição para a compreensão do conteúdo da matemática no âmbito escolar. Os autores estudados são Ubiratan D’Ambrósio, considerado o precursor do Programa Etnomatemática e pesquisadores como Paulus Gerdes, Maria do Carmo Santos Domite, Eduardo Sebastiani Ferreira e Gelsa Knijnik, que desenvolvem pesquisas nesta área e podem contribuir para a compreensão do que neste estudo pretendemos realizar. Ainda recorremos a autores de Educação e Filosofia da Educação como Maria Aparecida Viggiani Bicudo e Joel Martins para compreender a ideia de currículo e sua importância no âmbito escolar. O estudo efetuado mostrou que o Programa Etnomatemática vai além de explicitar os conhecimentos matemáticos produzidos por grupos culturais, transcendendo a descrição de procedimentos que revelam a construção do conhecimento atrelada às disciplinas escolares. Ou seja, o programa busca a valorização do ser humano, preocupando-se com a formação de um cidadão digno e capaz de se relacionar com seu ambiente natural, social e intelectual
Keywords: Matemática - Estudo e ensino; Etnomatematica